Mengatasi Masalah Low Self Esteem Siswa melalui Konseling Individu Model Person Centered Theraphy - Hanifah, Azmi; Hartati, Maria Theresia S. (Universitas Negeri Semarang, 2016)
This research applied based on the phenomenon in SMPN 25 Semarang which indicates several students who have low self-esteem, through the results of the DCM’s analysis distributed to the students of 9th grade. This research used to show the students’ self-esteem before and after having individual counseling model of person-centered Therapy and whether the model of person-centered Therapy counseling can overcome the problem of low self-esteem students. This research design is experimental research which using one group pretest-posttest design. The participants of this study were six students. The writer use Wilcoxon test as Hypothesis testing by comparing the level of the smallest of the pre and posttest. Obtained results Zcount 2,206 > Z table = 1.645, which means Ha accepted and Ho rejected. The research findings showed that (1) the pretest of the experiment of sixth counselees was 48.45% (2) In another hand the posttest result of the experiment sixth counselees was 75.65% (3) The problem of low self-esteem students can be solved through counseling models centered person theraphy. The result of the study shows that there is positive result and significant improvement of students’ self-esteem when teacher using Person Centered Therapy to solve low self-esteem problem.